PODCAST SEBAGAI MEDIA SUPLEMEN PEMBELAJARAN JARAK JAUH DI ERA PANDEMI - Rif’atul Himmah; Deony Dewanggi Mulyono; Fadilla Melati Melati (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2021)
Podcasts are programs in digital form (audio / video) that can be downloaded from the internet, and played on individual players and computers. Although podcasts provide many topics, generally the topics discussed are only shown in one episode. Not only in the field of communication, podcasts have now been studied for their use in the field of education. This article is written to outline the use of podcasts as a media supplement in distance learning, particularly in the pandemic era. The method used in this article is a literature review. The results show that podcasts in education can apply to a variety of contexts and learning objectives. Of course, pay attention to the format and type of podcast itself. In addition, podcasts also function in improving students' communication skills, learning motivation, and self-confidence.